Caracterización morfológica y evaluación agronómica - fenológica de tres variedades de papa nativa (Solanum spp.) provenientes de la provincia del Azuay - Condoy Tandazo, Marcos Guillermo (2024)
Subsistence farming families in the Andean zone are the ones that still conserve the diversity of native potato species. In the country there are between 500 to 350 varieties, of which, there is not adequate knowledge about their characteristics, only studies have focused on characterizing varieties of the central and northern highlands of the country. Therefore, the objective of this research was to characterize morphologically and agronomically three native potato varieties from the Azuay province. This consisted of recording qualitative and quantitative variables through a guide for basic morphological characterizations in native potato collections according to the International Potato Center (CIP) to know their genetic diversity and quality for consumption. According to the results, the flavor found in the varieties was pleasant and very pleasant, the texture moderately sandy and intermediate. Dry matter from 19.7 to 22.6 %, specific gravity 1.08 to 1.09 and the frying test indicated that one variety is suitable. The potato crop cycle lasted 119 days in the yellow bean (early type), 136 days in Santa Ana (medium type) and 164 days in Suscaleña (late type). The number of tubers per plant ranged from 17 to 32, the tuber yield per plant was 0.42 to 0.67 kg and the plant height ranged from 58 to 85 cm. The cultivation of native potatoes constitutes a human diet so it is important to emphasize its interest and nutritional importance, as well as in home gardens or chakras.